2013
DOI: 10.1007/s00439-013-1269-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with breast cancer risk for Ashkenazi Jewish women with strong family histories but no identifiable BRCA1/2 mutation

Abstract: Background The ability to establish genetic risk models is critical for early identification and optimal treatment of breast cancer. For such a model to gain clinical utility, more variants must be identified beyond those discovered in previous genome wide association studies (GWAS). This is especially true for women at high risk because of family history, but without BRCA1/2 mutations. Methods This study incorporates three datasets in a GWAS analysis of women with Ashkenazi Jewish (AJ) homogeneous ancestry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
17
2
Order By: Relevance
“…Interpreting these multiple risks constitutes another challenge to panel testing. Integrating SNP-associated risks has been based on additive models and has shown moderate discriminatory accuracy (Lalloo and Evans 2012;Rinella et al 2013). However the formalism for combining higher penetrance genetic risk variants to yield a composite risk score for multigenic diseases has not yet been developed (Ng et al, 2009;Swan et al 2010).…”
Section: Risk Estimatesmentioning
confidence: 99%
“…Interpreting these multiple risks constitutes another challenge to panel testing. Integrating SNP-associated risks has been based on additive models and has shown moderate discriminatory accuracy (Lalloo and Evans 2012;Rinella et al 2013). However the formalism for combining higher penetrance genetic risk variants to yield a composite risk score for multigenic diseases has not yet been developed (Ng et al, 2009;Swan et al 2010).…”
Section: Risk Estimatesmentioning
confidence: 99%
“…Our FGFR2 SNP, rs2981579, was first identified by Thomas et al [31] and independently replicated in two other GWAS [23, 32]. Other GWAS found stronger associations with other SNPs in the same gene [1, 7, 8, 10, 12, 15, 19, 22, 26]. Ahsan et al [1], for example, reported genome-wide significant p-values for 4 FGFR2 SNPs and young-onset breast cancer, with the smallest p-value seen for rs2981579.…”
Section: Methodsmentioning
confidence: 51%
“…87 articles were excluded because they clearly did not meet the criteria or overlapping references (Figure S1). Finally, a total of 26 eligible association studies were included involving 101,529 breast cancer cases and 167,363 controls [12], [20][44]. Of the cases, 80% were White, 12% were East Asian, 7% were African descent, and 1% were of other ethnic origins.…”
Section: Resultsmentioning
confidence: 99%